2022
DOI: 10.3389/fbioe.2022.867728
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Lethal Concentrations of Graphene Oxide Trigger Acute-Phase Response and Impairment of Phase-I Xenobiotic Metabolism in Upcyte® Hepatocytes

Abstract: The impact of graphene oxide on hepatic functional cells represents a crucial evaluation step for its potential application in nanomedicine. Primary human hepatocytes are the gold standard for studying drug toxicity and metabolism; however, current technical limitations may slow down the large-scale diffusion of this cellular tool for in vitro investigations. To assess the potential hepatotoxicity of graphene oxide, we propose an alternative cell model, the second-generation upcyte® hepatocytes, which show met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 83 publications
(165 reference statements)
0
10
0
Order By: Relevance
“…CYP1A1 and CYP39A1 genes encode members of the cytochrome P450 superfamily of enzymes, which catalyze reactions involved in drug metabolism. It was previously shown that GO interferes with drug metabolism/detoxification in the body at the level of phase I cytochrome-P450 system by the inhibition of gene expression and metabolic activity [ 64 ]. This influence of GO is clinically relevant, since altered drug metabolism can significantly contribute to the variability of drug responses and be associated with an increased risk of adverse effects along with altered detoxification.…”
Section: Resultsmentioning
confidence: 99%
“…CYP1A1 and CYP39A1 genes encode members of the cytochrome P450 superfamily of enzymes, which catalyze reactions involved in drug metabolism. It was previously shown that GO interferes with drug metabolism/detoxification in the body at the level of phase I cytochrome-P450 system by the inhibition of gene expression and metabolic activity [ 64 ]. This influence of GO is clinically relevant, since altered drug metabolism can significantly contribute to the variability of drug responses and be associated with an increased risk of adverse effects along with altered detoxification.…”
Section: Resultsmentioning
confidence: 99%
“…In an alternative cell model to primary human hepatocytes, GO (with average size of 360 nm) at 80 μg/mL for 24 h was found to activate early apoptosis but not oxidative stress or inflammation. 312 In addition, this GO material impaired cytochrome P450 phase-I drug metabolism enzymes, but it had no effect on phase-II enzyme GST or phase-III efflux transporter ABCG2. Phase-I drug metabolism enzyme alteration was associated with the alteration of gene expression and protein levels for several acute-phase proteins.…”
Section: Impact On Liver Spleen and Kidneysmentioning
confidence: 94%
“…GO also stimulated protein expression of αSMA, a biomarker of fibrosis via modulation of the TGFβ pathway. In an alternative cell model to primary human hepatocytes, GO (with average size of 360 nm) at 80 μg/mL for 24 h was found to activate early apoptosis but not oxidative stress or inflammation . In addition, this GO material impaired cytochrome P450 phase-I drug metabolism enzymes, but it had no effect on phase-II enzyme GST or phase-III efflux transporter ABCG2.…”
Section: Impact On Liver Spleen and Kidneysmentioning
confidence: 99%
“…Second-generation UHHs (derived from the donor 653–03; upcyte® Technologies GmbH, Hamburg, DE) were cultured as previously reported by Romaldini et al 44 After thawing, cells were expanded for 2 passages in collagen-coated tissue culture flasks (VWR, Radnor, PA, USA) and, at passage 3 (P3), were treated with the PC-NP dispersions in collagen-coated flat bottom 24- or 96-well plates (Corning Incorporated, Corning, NY, USA) as described below. At P3, the number of viable cells was higher than 92.9%, as revealed by the trypan blue (Sigma Aldrich-Merck KGaA, Darmstadt, DE) exclusion test.…”
Section: Methodsmentioning
confidence: 99%